TechTasker: electronic device repairing digital platform connecting device owner and freelance repairmen - Ahmad Dahlan, Abdul Rahman; Sakib, Nazmus; Hossain, Tahmeed Anjum (IJSRP.org, 2018)
The purpose of this paper is to propose a conceptual digital platform where it is possible to connect malfunctioned electronic device owners and the repairmen to get the repairing done. This is a Consumer-to-Consumer (C2C) business model where the malfunctioned electronic device owners will be able to find a repairman to repair their devices. On the other side, for the freelance repairmen this solution will enable them to find clients easily and effectively. As people feel hectic to go shopping in repairing their devices, the proposed digital platform shall become a convenient platform.